THE CHALLENGES OF COMMUNITY-BASED EDUCATION IN CREATING INCLUSIVE EDUCATION FOR MARGINALIZED GROUPS. A CASE STUDY OF MASJID TERMINAL SCHOOL, DEPOK CITY - Ulpah, Mariam; Windiana, Wiwin; Junejo, Safiullah; Nugraha, Muhammad Iqbal (Politeknik Siber Cerdika Internasional, 2024)
The MASTER School (terminal mosque) is a free school founded by community representatives focusing on inclusive schools for marginalized people from low-income families in the Depok area, West Java. This school is considered to support the government's strategic plan to provide education for all. However, realizing the lack of the government's role in equalizing access to education, this paper attempts to answer the question: What factors are initiatives for MASTER schools to consider when developing inclusive education for marginalized groups through community-based education? How does MASTER school develop inclusive education for marginalized groups through community-based education? The method in this research is qualitative with a case study approach. The data was collected from interviews and observations of schools and classes, as well as from relevant journals and articles, sist research analysis. The findings of this paper show that several factors contributed to the establishment of the MASTER school, including social awareness, which is generated by self-designed school founders motivated by the surrounding social environment. In addition, the inclusive education implemented at the MASTER school is based on a narrow understanding of the differences between children in the same room and pro. It provides education without the support of adequate facilities and teachers. In addition, there still needs to be more understanding of educational inclusion, which is also a challenge for its implementation.